2019
DOI: 10.3389/fphys.2019.01344
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cholesterol Sulfate/Seminolipid Ratio in Semen Lipid Profile of Men With Oligoasthenozoospermia

Abstract: The reduction of sperm motility and count, or oligoasthenozoospermia, is one of the major causes of reduced fertility or infertility in men. Lipid composition of spermatozoa is important in determining their functional characteristics, in particular on motility, acrosomal exocytosis or fusogenic properties of the sperm. Here we investigated the levels of semen lipids in 11 infertile patients with severe oligoasthenozoospermia and 9 normozoospermic subjects with normal motility values. Sperm polar and neutral l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Seminal plasma triglyceride, total cholesterol, low-density lipoprotein, and high-density lipoprotein levels in patients with impaired spermatogenesis were higher than in patients with normal sperm concentration, motility, or morphology. An investigation of the lipid composition of human semen showed a significant higher cholesterol sulfate/seminolipid ratio in semen of oligoasthenozoospermic patients than in subjects with normal motility values (Lopalco et al, 2019). In line with the above reported data, another study showed that the cholesterol level in seminal plasma was positively associated with sperm concentration, total sperm count, sperm motility, and morphology, but there was no association between serum cholesterol and the tested semen parameters (de Neergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…Seminal plasma triglyceride, total cholesterol, low-density lipoprotein, and high-density lipoprotein levels in patients with impaired spermatogenesis were higher than in patients with normal sperm concentration, motility, or morphology. An investigation of the lipid composition of human semen showed a significant higher cholesterol sulfate/seminolipid ratio in semen of oligoasthenozoospermic patients than in subjects with normal motility values (Lopalco et al, 2019). In line with the above reported data, another study showed that the cholesterol level in seminal plasma was positively associated with sperm concentration, total sperm count, sperm motility, and morphology, but there was no association between serum cholesterol and the tested semen parameters (de Neergaard et al, 2018).…”
Section: Discussionmentioning
confidence: 62%
“…Besides being the most abundant steroidal sulfoconjugate present in human plasma, with an average concentration of 2 μM (Meng, Griffiths, Nazer, Yang, & Sjövall, 1997), CS has also been detected in other biological fluids, such as urine, bile, seminal plasma, and in many tissues, as described previously (Castellanos, Hernandez, Tomic-Canic, Jozic, & Fernandez-Lima, 2020;Drayer & Lieberman, 1967;Lopalco et al, 2019;Strott & Higashi, 2003). Even though CS is typically considered the hydrophilic excretion form of cholesterol, CS also represents a biosynthetic precursor of several bioactive steroids.…”
Section: Cholesterol-3-sulfatementioning
confidence: 84%
“…Interestingly, Masaki et al demonstrated that the alteration of TG metabolism, obtained by the deletion of the Atgl gene, affects spermatogenesis and the maturation process of the male gamete 43 . Seminolipids are sulfogalactosylglycerolipids 44,45 selectively and very abundantly found in the sperm plasma membrane of mammals including humans 46,47 . They are essential for completion of the spermatogenesis, fertilization, and sperm–egg interactions 47 .…”
Section: Resultsmentioning
confidence: 99%
“…41 43 Seminolipids are sulfogalactosylglycerolipids 44,45 selectively and very abundantly found in the sperm plasma membrane of mammals including humans. 46,47 They are essential for completion of the spermatogenesis, fertilization, and sperm-egg interactions. 47 In the mouse testis, Goto-Inoue et al showed that SL(16:0/16:0) was detected throughout the tubules, whereas SL(16:0/14:0) was mainly found in spermatocytes and SL(17:0/16:0) specifically expressed in spermatids and spermatozoa using IMS.…”
Section: D Model Constructionmentioning
confidence: 99%